Can teacher collaboration improve students' academic achievement in junior secondary mathematics? / Owodunni Adewale Saka - Saka, Owodunni Adewale (Universiti Teknologi MARA, 2021)
The unsatisfactory students' performance in school subjects in Nigerian secondary schools has been blamed on teachers' quality and professional development suggested as a remedy. Hence, this study examined the effects of teacher collaboration on students' academic achievement in mathematics. The study adopted pretest-posttest-control group quasi-experimental design involving a 2x2 factorial matrix. The sample for the study consisted of one hundred and thirty-five (135) students from two intact classes and five teachers of the two junior secondary schools purposively selected for the study. Mathematics Achievement Test (MAT), a researcher-developed instrument with reliability coefficient of 0.86 was used to collect data. The collected data were analyzed using both descriptive and inferential statistics. The results indicated significant difference in the effect of teachers' group (collaboration and isolation) on students' achievement in mathematics. Also, the study found no significant effect of students' age on academic achievement in Mathematics. Additionally, the finding revealed no significant interaction effect of teachers' group and students' age on academic achievement in Mathematics. Based on the findings, the study recommended among other that government should restructure the school hours to cater for teacher collaboration activities and that workshops should be organised for teachers on the importance of teacher collaboration as a means of professional development.